203k views
4 votes
Which of the following is a root of the polynomial shown below?

f(x) = x2 + 2x2 - x-2
O A. 1
OB. 3
O c. O
O D. 2

User Kala
by
5.3k points

1 Answer

3 votes

Answer:

We conclude that option A is true as x = 1 is the root of the polynomial.

Explanation:

Given the polynomial


f\left(x\right)\:=\:x^2\:+\:2x^2\:-\:x-2

Let us determine the root of the polynomial shown below.


\:0=\:x^2\:+\:2x^2\:-\:x-2


0=3x^2-x-2

switch sides


3x^2-x-2=0

as


3x^2-x-2=\left(3x+2\right)\left(x-1\right)

so the equation becomes


\left(3x+2\right)\left(x-1\right)=0

Using the zero factor principle


3x+2=0\quad \mathrm{or}\quad \:x-1=0

solving


3x+2=0


3x=-2


(3x)/(3)=(-2)/(3)


x=-(2)/(3)

and


x-1=0


x=1

The possible roots of the polynomial will be:


x=-(2)/(3),\:x=1

Therefore, from the mentioned options, we conclude that option A is true as x = 1 is the root of the polynomial.

User JYL
by
5.9k points